Does the Interaction Between Cortisol and Testosterone Predict Men’s Facial Attractiveness? - Kandrik, Michal (Adapt Human Behav Physiol, 2017)
Although some researchers have suggested that the interaction between cortisol and testosterone predicts ratings of men’s facial attractiveness, evidence for this pattern of results is equivocal. Consequently, the current study tested for a correlation between men’s facial attractiveness and the interaction between their cortisol and testosterone levels. We also tested for corresponding relationships between the interaction between cortisol and testosterone and ratings of men’s facial health and dominance (perceived traits that are correlated with facial attractiveness in men). We found no evidence that ratings of either facial attractiveness or health were correlated with the interaction between cortisol and testosterone. Some analyses suggested that the interaction between cortisol and testosterone levels may predict ratings of men’s facial dominance, however, with testosterone being more closely related to facial dominance ratings among men with higher cortisol. Our results suggest that the relationship between men’s facial attractiveness and the interaction between cortisol and testosterone is not robust. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s40750-017-0064-1) contains supplementary material, which is available to authorized users.